How to Stimulate Student's Critical Thinking Skill on Learning Electrical Conversion Energy? - Suyanto, Eko; Wijaya, Karina; Maulina, Hervin; Andra, Doni (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2021)
One alternative for students to actively participate in education is to teach material through a practicum with a thermal-electric energy conversion tool equipped with Student Worksheet (SW). This matter shows that SW is a crucial subject to develop. This research aims to develop SW to stimulate students' critical thinking skills in the heat-electric energy conversion material. The research design used is ADDIE. The validity test instrument measures the validity of the SW by the expert and the small group test. The validity test results and the small group test show that the developed SW is valid and able to stimulate critical thinking skills so that the resulting SW is suitable to be used as an alternative moderate in learning material for thermal-electric energy conversion.